Mothering in the Aftermath of Reproductive Coercion and Abuse - McKenzie, Mandy (Violence against women, 2025)
A partner's reproductive coercion and abuse (RCA) can significantly undermine women's physical health and psychological wellbeing. Yet little research has explored how RCA affects experiences of mothering and relationships with children. Based on an analysis of interviews with 30 Australian mothers, we found that RCA affected mothering in complex ways. Many struggled with feeling detached, resentful, and guilty toward their children, while some found mothering an emotionally and morally restorative experience after the RCA. All felt compelled to conceal their abuse from their children and others. The findings have implications for how healthcare practitioners can support mothers in the aftermath of RCA.